2016
DOI: 10.4172/2155-9570.1000544
|View full text |Cite
|
Sign up to set email alerts
|

Change in Axial Length Pre and Post Cataract Surgery Measured with IOL Master

Abstract: Objective: Cataract surgery with intraocular lens (IOL) implantation tries to get a refractive result nearby to the optic emmetropia. So an accurate IOL power calculation is mandatory, and axial length (AL) measurement is one of the most influential parameter in this calculation. IOL Master is one of the most popular devices to measure AL, which uses the same group refractive index of the lens for all patients, independently of the cataract grade. But lens refractive index is higher as cataract grade increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Several contradictory results were published regarding AL shortening in patients who underwent phacoemulsification surgery. 8,26 We found no post-phacoemulsification change regarding the AL of either group by performing measurements with IOL Master 700 (Carl Zeiss Meditec, Jena, Germany), in order to avoid errors as explained previously by Bernardo et al 27 Concerning the AL, our results are in accordance with those found by Bernardo and Lopez 27,28 and not with the results published by Bilak, Chang and Kim. 8,26,29 We consider our follow-up period of 6 months as an important element of our study, as previous similar research carried out had a shorter follow-up period of 1-3 months (Table 4).…”
Section: Discussionsupporting
confidence: 82%
“…Several contradictory results were published regarding AL shortening in patients who underwent phacoemulsification surgery. 8,26 We found no post-phacoemulsification change regarding the AL of either group by performing measurements with IOL Master 700 (Carl Zeiss Meditec, Jena, Germany), in order to avoid errors as explained previously by Bernardo et al 27 Concerning the AL, our results are in accordance with those found by Bernardo and Lopez 27,28 and not with the results published by Bilak, Chang and Kim. 8,26,29 We consider our follow-up period of 6 months as an important element of our study, as previous similar research carried out had a shorter follow-up period of 1-3 months (Table 4).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in accordance with several other reports. [12][13][14][15] The cause of the apparent shortening has been debated. As previously suggested, one explanation might be the index calibration of the IOLMaster readings; the dark horse being the crystalline lens, the refractive index of which is largely unknown.…”
Section: Discussionmentioning
confidence: 99%